(untitled) (Web of Teachers: Inderscience Research, 2025)
This article is devoted to measure current issues of uzbek girls’ upbringing and giving some advice how to raise children especially girls in our country. The article analyzes the problems of teaching how girls should behave properly in both family and society. The author informs some promising researches in this direction.